Sustained release of miR-21 carried by mesenchymal stem cell-derived exosomes from GelMA microspheres inhibits ovarian granulosa cell apoptosis in premature ovarian insufficiency - Xiaofei Zhang; Linzi Ma; Xiaotong Liu; Xingyu Zhou; Ao Wang; Yunhui Lai; Jun Zhang; Ying Li; Shiling Chen (Materials Today Bio)
Background: Premature ovarian insufficiency (POI) refers to the severe decline or failure of ovarian function in women younger than 40 years of age. It is a serious hazard to women's physical and mental health, but current treatment options are limited. Mesenchymal stem cell-derived exosomes (MSC-Exo) exhibit promising potential as a therapeutic approach for POI. However, their clinical application is hindered by their instability and low long-term retention rate in vivo. Methods and results: In this study, miR-21 was identified as the predominant miRNA with low-expression in follicular fluid exosomes of POI patients and was shown to possess antiapoptotic activity. Next, we loaded miR-21 agomir to MSC-Exo to form Agomir21-Exo, which significantly reversed the apoptosis of granulosa cells in vitro. Moreover, we successfully developed GelMA hydrogel microspheres for encapsulating Agomir21-Exo through microfluidic technology, named GelMA-Ag21Exo, which had good injectability and significantly enhanced the stability and long-term retention of Agomir21-Exo in mice through sustained release. The release of Agomir21-Exo from GelMA-Ag21Exo notably alleviated the apoptosis of ovarian granulosa cells and improved the ovarian reserve and fertility in POI mice. Conclusion: Our findings illustrate that activating miR-21 through Agomir21-Exo could improve the function of ovarian granulosa cells. The GelMA-Ag21Exo enhanced the exosome-based therapeutic efficacy of the Agomir21-Exo in vivo. These findings provide a novel and promising treatment strategy for POI patients.